Verbal Bullying In The Greatest Showman Movie Directed By Michael Gracey - Anggraini Anggraini; Unpris Yastanti; Astrida Khairani (Universitas Batanghari Jambi, 2020)
The purpose of the research in this movie is to determine the cause of verbal bullying and the effect of verbal bullying in the movie The Greatest Showman, directed by Michael Gracey. This method of research uses a qualitative approach. To analyze the movie the writer watched the movie several times and used the theory of books or online journals. In The movie The Greatest Showman there is a verbal violent scene such as (1) Taunting (2) A feeling of resentment (3) Hostility (4) Contempt. While the effect of bullying against victims is (1) Decreasing confidence (2) Feeling intimidate (3) Feeling isolated (4) Prolonged depression (5) Feeling dissimilar (6) Feeling stress. The results of this research are (1) the cause of verbal bullying are hostility,A sense of lack od confidence anf attentian seeking, A feeling of resentment, the Negative influence of media.(2) The Effect of bullying are Feeling disimilar and Decreasing confidence.